Pengaruh Kata-Kata Unik Makanan Umkm Terhadap Citra Brandnya - Aimee Natalia Tampi (Universitas Katolik Soegijapranata, Semarang, 2018)
This paper discusses the influence of unique words on SME’s food on SME brand, becausemany SME’s food packaging made with the same form, same color even the same words,slogan, and that is often make a buyer difficult to choose when they forgot the brand’s namethey want to buy. Researchers , in this paper was to investigate how the effect of uniquewords on the image of the SME’s brand with the help of the theories that have been there ,interviews with experts design , in this case the researcher describes how the unique wordsare good to use in improving the image of the brand , in an interview with design experts ,researchers found that in enhancing the brand image of SME,SME can use unique words asthe first step of their markerting , which brought the paper to the end of the discussionstating that words can uniquely affect the image of a brand.